The family as an entity in the polish legal order = La famille en tant qu’entité juridique dans l’ordre juridique polonais = La famiglia come soggetto nell’ordine giuridico polacco - Poniatowski, Michał Jerzy (Philosophy & canon law, 2017)
The concept of the family as a legal entity in the Polish legal order, discussed in this paper, concerns practical issues that are at the same time quite complex, due to the vague and inconsistent definition of the status of the family in particular branches of law, which enjoy their own autonomy within the framework of the current system of universally applicable law. Proper understanding of the issue in question requires an adequate analysis of legal provisions, judicial decisions, and the literature. The article presents the subject matter in the context of traditional branches of law such as constitutional law (in addition to international and community law, which recognize a number of family rights and obligations), administrative law, civil law, and penal law. As a consequence of adopting such article structure, in individual parts thereof the issue of family as a legal entity is presented in both substantive and formal context, accompanied by the relevant conclusions. The final section of the paper contains the most important general conclusions resulting from the analysis.